2006
DOI: 10.1179/174329306x84300
|View full text |Cite
|
Sign up to set email alerts
|

Laser pressure welding of Al alloy and low C steel

Abstract: This study was performed to obtain fundamental knowledge concerning the development of laser pressure welding technology for the joining of dissimilar metals. Laser pressure welding of Al alloy A6061 and low C steel SPCC sheets was carried out to investigate the effects of the roller pressure, laser beam scanning speed and irradiation position on the tensile shear and peel strength of welded joints. The interfaces of the joints were observed and analysed by SEM and EDX, and the formation phases on the peeled s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 6 publications
0
14
0
Order By: Relevance
“…Autogenous ''braze welding'' [4,5], laser pressure welding [6][7][8][9] in which pressure was simultaneously applied with laser irradiation, and filler-metal-added braze welding [10][11][12][13][14][15][16] have been considered. In these studies, only the Al alloy was melted, while the steel remained unmelted.…”
Section: Introductionmentioning
confidence: 99%
“…Autogenous ''braze welding'' [4,5], laser pressure welding [6][7][8][9] in which pressure was simultaneously applied with laser irradiation, and filler-metal-added braze welding [10][11][12][13][14][15][16] have been considered. In these studies, only the Al alloy was melted, while the steel remained unmelted.…”
Section: Introductionmentioning
confidence: 99%
“…There was also inconsistency across reviews regarding the description of comparison physiotherapy treatment within the Obrien et al 2006 [32] study. Pereira et al (2012) [8] defined the type of physiotherapy as lumbar stabilisation exercise, while Lim et al (2006) [7] reported that the physiotherapy treatment included other modalities as well.…”
Section: Resultsmentioning
confidence: 99%
“…Timing of evaluation was dependent on the duration of the Pilates treatment and the length of follow up. The shortest follow up was at 6 weeks [28,31,32] and longest follow up assessment was at 12 months following the completion of Pilates treatment [24,25,30]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[2,3] As a unique kind of energy source, laser beam provides some attractive advantages, including high power density, small heating area, rapid heating/cooling rate, and low heat input, which are beneficial in inhibiting the formation of IMCs. In recent years, several laser-assisted joining processes have received more attention; these include laser-assisted roll bonding, [4] laser pressure welding, [5] laser-induced reactive wetting without filler metal (only irradiating Al sheet to melt it), [6] laser brazing (only irradiating filler metal wire or steel sheet to melt filler metal by direct heating or heat conduction through the hot steel sheet), [7][8][9] and laser braze welding (irradiating both filler metal wire and Al sheet to melt and mix them). [10,11] For laser-assisted joining processes, shielding gas (argon) [6][7][8][9][10][11] or brazing flux (e.g., fluor-base anticorrosive brazing flux [6][7][8]11] ) is necessary, although satisfactory strength can be obtained by optimizing filler metal (e.g., using Zn filler metal instead of the Al base one [9,10] ) and process parameters.…”
Section: Introductionmentioning
confidence: 99%